Exploring the size of Andean condor foraging groups along an altitudinal and latitudinal gradient in the Tropical Andes: Ecological and conservation implications - Méndez, Diego (2023)
Patterns of variation in the size of vulture foraging groups, and their ecological causes and consequences, remain little explored despite strong links with the carrion recycling service that this key functional group provides. We documented the group size-frequency pattern of Andean condors Vultur gryphus gathered to feed on 42 equine carcasses experimentally placed in Bolivia, between 2012 and 2019, along an elevation range of 1,300–4,500 m asl. Based on the location (altitude and latitude) of the foraging groups, we examined the relationship between their size and species’ population parameters (size and trend), habitat conditions, and livestock carcass availability and predictability. Condors utilized a high frequency (93%) of carcasses forming groups that ranged from 1 to 80 individuals (mean = 25, median = 18) and shaped a “lazy-J curve” typical pattern of size-frequency distribution whereby few groups (5, 12%) were large (> 55 individuals) and most (21, 50%) were relatively small (<19 individuals). Group size related to altitude in that most larger groups formed at lower sites (below c. 3,000 m asl), likely following an altitudinal gradient whereby larger groups are more likely to form around larger carcasses (i.e., cattle), which are more likely to occur at lower elevations. Regardless of population size, group size could be an adaptive response of condors via local enhancement for improving individual scavenging efficiency. Many information gaps on this topic still exist, thus we provide a set of questions to address them, especially amidst the unrestricted impacts of human activities that condition vulture survival globally.